"I Believe Because it is Absurd": The Enlightenment Invention of Tertullian's Credo. Issue 2 (10th August 2017) - Harrison, Peter
Abstract : Tertullian is widely regarded as having originated the expression Credo quia absurdum (est) (I believe because it is absurd) and the phrase often appears in contemporary polemics about the rationality of religious belief. Patristic scholars have long pointed out that Tertullian never said this or meant anything like it. However, little scholarly attention has been paid to the circumstances in which this specific phrase came into existence and why, in spite of its dubious provenance, it continues to be regarded by many as a legitimate characterization of religious faith. This paper shows how Tertullian's original expression—"It is certain, because impossible"—was first misrepresented and modified in the early modern period. In seventeenth century England a " credo " version— I believe because it is impossible—became the common form of Tertullian's maxim. A further modification, building on the first, was effected by the Enlightenment philosophe Voltaire, who added the "absurdity condition" and gave us the modern version of the paradox: I believe because it is absurd . These modifications played a significant role in Enlightenment representations of religion as irrational, and signal the beginning of a new understanding of faith as an epistemic vice. This doubtful maxim continues to play a role in debates about the cognitive status of religious faith, and its failure to succumb to the historical evidence against it is owing to its ongoing rhetorical usefulness in such debates.